Review of performance studies of direct coupled photovoltaic water pumping systems and case study. (September 2017) - Chandel, S.S.; Naik, M. Nagaraju; Chandel, Rahul
Abstract: Solar water pumping is an attractive option for irrigation and drinking water supplies in view of increasing diesel costs and grid electricity scarcity. Currently direct coupled DC and AC solar run water pumps are extensively used worldwide. The main objective of this study is to review the performance studies of direct coupled photovoltaic water pump systems (PVWPS) along with a case study of an old functional solar water pump after prolonged outdoor exposure in a western Indian Himalayan location. The updated review critically examines PVWPS performance studies, optimum sizing and the use of electronic controls to improve the efficiency. The intelligent control methods for maximum power point tracking (MPPT) of PV systems are found to improve the PVWPS efficiency under outdoor temperature and irradiance conditions. The techno-economic analysis of PV and diesel pumping shows that PV-based water pumping is more cost-effective than diesel-powered pumping. The study shows that PVWPS are cost effective with little maintenance for water pumping requirements. The case study on the performance evaluation of an old direct coupled DC solar pump shows that only two modules of its mono-crystalline PV generator have degraded substantially after 28 years of field operation affecting its performance. The PV degradation rate is found to be 1.4% per year which is comparable to the reported degradation rate of 1.45% for mono crystalline in India. The system is still found to be capable of generating enough power to pump water at average rate of 829 l/h. The experimental performance results are found to be in close agreement with the simulated results. The performance of PVWPS is found to improve when installed at an optimum tilt angle for the location. These are first time reported results of significance to assess the state of PV pumping technology after a prolonged outdoor exposure for further research.